Molecular mechanisms involved in the immunomodulatory action of Baccharis dracunculifolia DC. extract using an integrated in silico/in vitro approach - Cappellucci, Giorgio; Biagi, Marco; Romão-Veiga, Mariana [UNESP]; Ribeiro-Vasques, Vanessa Rocha [UNESP]; Miraldi, Elisabetta; Baini, Giulia; Sforcin, José Maurício [UNESP] (Oxford University Press (OUP), 2025)
OBJECTIVES: Ethnobotany and the traditional use of medicinal plants is still a key starting point for the discovery of new drugs in modern medicine, despite often being underrated. Baccharis dracunculifolia DC., the major source of green propolis, has been traditionally used in South America for the treatment of malaria and parasitic infections, and for liver and gastric disorders. To investigate the molecular mechanisms involved in its immunomodulatory action, an integrated in silico/in vitro model was developed and validated. METHODS: The phytochemical profile of a hydro-ethanolic dry extract of B. dracunculifolia was investigated through UV-vis and HPLC-DAD methods and implemented with LOTUS database. Through simulated digestion and computational approaches, such as Network Pharmacology, pharmacokinetics, and biological targets were predicted. To validate bioinformatic predictions and to assess the immunomodulatory potential of B. dracunculifolia extract, in vitro tests were conducted on human monocytes (THP-1) and on peripheral blood mononuclear cells (PBMC) through ELISA dosage and flow cytometry. KEY FINDINGS: Terpenoids resulted the most enriched class in Baccharis dracunculifolia extract (BDE) (>25% w/w), followed by phenolics compounds (>15% w/w) which also included artepillin C, caffeic acid derivatives, pinocembrin, and pinobanksin. With the exception of pinocembrin, most of BDE constituents displayed a limited bioaccessibility rate. MAPK, NF-κB, several cytokines and TLR-4 were identified as key targets. These predictions were experimentally validated, as B. dracunculifolia extract, particularly 25 μg/ml, showed to upregulate MAPK ERK1/2 and p38 activation, to modulate NF-κB and to modulate cytokine release, particularly in PBMCs, where IL-1β, IL-10, IL-6, and IL-2 increased by 27%, 39%, 17%, and 21% vs control, respectively, under basal conditions, while in the inflammatory model, it caused a selective 59% reduction in Tumor necrosis factor alpha (TNF-α) vs lipopolysaccharide (LPS). This approach provided valuable guidance for experiments while reducing both cost and time. CONCLUSIONS: Our findings demonstrated that the integrated in silico/in vitro approach proved to be a valuable and cost- and time-efficient tool for studying B. dracunculifolia extract, which was shown to exert immunomodulatory activity by modulating multiple signaling pathways at both upstream and downstream levels.